Electromyography and Nerve Conduction Study in Predicting Functional Outcome in Paediatric Patients with Guillain-Barre’ Syndrome - BABAR, M J; HUMAYUN, A (Annals of King Edward Medical University, 2017)
A prospective study from January-1999 to March-2001 including 33 consecutive children with Guillain Barre’ Syndrome (GBS) admitted in the Children’s Hospital Lahore. Electromyography (EMG) and Nerve Conduction Study (NCS) were performed at 2l day post onset of weakness or earlier, as required to confirm the type of lesion- whether segmental demyelination alone or segmental demyelination along with axonal degeneration. Reduction in conduction velocity, conduction block or abnormal temporal dispersion, prolonged distal motor latencies, absent or prolonged F-wave latencies were indicative of segmental demyelination. The presence of profuse fibrillation potentials in muscles were indicative of axonal degeneration. All patients who underwent in-patient rehabilitation management were followed up for their neurological and functional status on admission and discharge. The outcome results compared between the two groups. The Modified Functional Independence Measure (MFIM) was used as an assessment tool for evaluating functional status. A good neurological recovery, higher functional independence scores and early discharge was noted in children having segmental demyelination alone. Whereas in children with the axonal variety of the disease who had a more complicated course requiring assisted ventilation at times, poor or delayed neurological recovery and prolonged rehabilitation time were noted. These findings suggest that EMG & NCS is a helpful tool ¡n the diagnosis, prognosis and better management of children with acute GBS.